Quantitation of telomerase components and hTERT mRNA splicing patterns in immortal human cells - Yi, Xiaoming (Oxford University Press, 2001)
Telomerase is a reverse transcriptase that adds telomeric repeats to chromosomal ends. In most normal human somatic cells, telomerase is repressed and telomeres progressively shorten, leading to limited proliferative life-span. Telomerase reactivation is associated with cellular immortalization and is a frequent event during tumorigenesis. The telomerase ribonucleoprotein complex consists of two essential components, a catalytic protein subunit [human telomerase reverse transcriptase (hTERT)] and a template RNA (hTR). hTR is constitutively expressed, while hTERT is almost universally absent in telomerase-negative cells. Although repression of telomerase is transcriptional in telomerase-negative cells, post-transcriptional and assembly processes are likely to play important roles in regulating telomerase activity in those that are telomerase-positive. The telomerase transcript can also be alternatively spliced into a variety of non-functional forms. To establish the quantitative relationships between telomerase activity and its various components, we determined the numbers of molecules of hTR and hTERT mRNA, and the levels of alternatively spliced hTERT mRNA variants in normal, in vitro immortalized and cancer cell lines. We report here that there is surprisingly little variation in the proportion of alternatively spliced forms of hTERT in different cell lines. The only variation observed occurred when a change in splicing to non-functional forms appeared in response to conditions that repress telomerase activity in IDH4 cells. We also found that most telomerase-positive cell lines only contain a few molecules of potentially functional hTERT mRNA, and there is a correlation between telomerase activity and the levels of both hTR and hTERT +α+β mRNA.